2010
DOI: 10.2111/rem-d-09-00141.1
|View full text |Cite
|
Sign up to set email alerts
|

Growth Regulator Herbicides Prevent Invasive Annual Grass Seed Production Under Field Conditions

Abstract: Growth regulator herbicides, such as 2,4-D, dicamba, picloram, and aminopyralid, are commonly used to control broadleaf weeds in rangelands, noncroplands, and cereal crops. If applied to cereals at late growth stages, while the grasses are developing reproductive parts, the herbicides often reduce cereal seed production. We are researching methods for using this injury response to control invasive annual grasses in rangelands by depleting their short-lived seed banks. In a previous greenhouse study, we found p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
0
16
2
Order By: Relevance
“…Aminopyralid was included in the tebuthiuron treatments as an experimental tank mix. Due to lack of downy brome control by aminopyralid in previous field studies and for the sake of brevity, this treatment will be referred to as tebuthiuron (Rinella et al 2010). Imazapic treatments included 1.3% v·v -1 methylated seed oil, while glyphosate and tebuthiuron treatments included 0.25% v·v -1 non-ionic surfactant.…”
Section: Integrating Prescribed Burning With Herbicidesmentioning
confidence: 99%
“…Aminopyralid was included in the tebuthiuron treatments as an experimental tank mix. Due to lack of downy brome control by aminopyralid in previous field studies and for the sake of brevity, this treatment will be referred to as tebuthiuron (Rinella et al 2010). Imazapic treatments included 1.3% v·v -1 methylated seed oil, while glyphosate and tebuthiuron treatments included 0.25% v·v -1 non-ionic surfactant.…”
Section: Integrating Prescribed Burning With Herbicidesmentioning
confidence: 99%
“…Research on annual invasive plants focuses on various sexual reproduction aspects, shaping the dynamics of the population. At present, the number of studies concerning flowering phenology (Suzuki et al 2007), fruit and seed production (MolinaMontenegro et al 2008;Rinella et al 2010), propagule size (Fumanal et al 2007) and seedling recruitment (Fumanal et al 2008). Despite growing interest in the aforementioned issues, the present state of knowledge on numerous taxa remains unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the data presented in the study (from literature and experimental components) showed that, for 19 species of seven families sprayed with glyphosate, there is an effect on vegetative parts as well as on the next generation. Rinella et al (2010b) investigated the possibility of using plant growth regulators to control invasive annual grasses by depleting their short-living seed banks. It was reported that reduced cereal grain yield was observed when plant growth regulators were applied in cereal (Triticum aestivum, Hordeum vulgare, Zea mays and Avena sativa) fields at late growth stages (Friesen et al, 1968;Sikkema et al, 2007;Rinella et al, 2010b).…”
Section: Duration Of the Testmentioning
confidence: 99%
“…Rinella et al (2010b) investigated the possibility of using plant growth regulators to control invasive annual grasses by depleting their short-living seed banks. It was reported that reduced cereal grain yield was observed when plant growth regulators were applied in cereal (Triticum aestivum, Hordeum vulgare, Zea mays and Avena sativa) fields at late growth stages (Friesen et al, 1968;Sikkema et al, 2007;Rinella et al, 2010b). In two greenhouse studies, Rinella et al (2010a) investigated the effect of 2,4-D (at 1.12 kg a.i./ha), dicamba (at 0.56 kg a.i./ha) and picloram (at 0.42 kg a.i./ha) on the invasive annual grass Bromus japonicus at four different developmental stages (seedling, initiation of internode elongation, boot, and heading; Rinella et al, 2010a).…”
Section: Duration Of the Testmentioning
confidence: 99%